Wars, internal conflicts, and political order : a Jewish democracy in the Middle East - Barzilai, Gad (State University of New York Press, 1996)
Annotation This is the first comprehensive research study to analyze and explain the influence the prolonged Arab-Israeli conflict has had on Israel. It focuses on the manner in which all of the Israeli-Arab wars since 1949, including the Intifada and the Gulf War, have affected state and society in Israel. In addition, it examines the influences of other, more limited Israeli military operations.
Keywords: Israel -- History, Military.; Arab-Israeli conflict.; War and society -- Israel.; Politics and war.; Democracy -- Israel.; Conflit israélo-arabe.; Guerre et société -- Israël.; Politique et guerre.; HISTORY.; Arab-Israeli conflict; Democracy; Politics and war; War and society; Israel; Military history